Development of a regression model to forecast ozone concentration in Istanbul City, Turkey - Tecer, LH; Ertürk, F; Cerit, O (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2003)
In this study, an air quality model including pollutants (NOx, non methane hydrocyarbons (NMHC)) and meteorological parameters (wind speed, solar radiation, rain, relative humidity and temperature) has been developed for the formation of ozone in Istanbul City. This model has been used to predict the daily ozone concentrations at different time periods and to examine various control strategies. The ozone prediction model sufficiently explained the change of diurnal and seasonal ozone formation. The diurnal pattern of ozone increases from 12 at noon to 4 a.m. Moreover, the seasonal change of ozone has increased from April to July and reached its maximum level in August. In July and August, the mean ozone concentrations were 11.4 and 10.3 ppb, respectively. In the period of the study, the measurement of the ozone showed that the exposition level to photochemical smog was relatively lower than in other Metropolitan Areas of the world.
Keywords: photochemical smog; predicting of ozone; regression model; ATMOSPHERIC PHOTO-OXIDATION; STATISTICAL TREND ANALYSIS; TIME-SERIES ANALYSIS; AIR-QUALITY DATA; ORGANIC-COMPOUNDS; TROPOSPHERIC CHEMISTRY; INCREMENTAL REACTIVITIES; STOCHASTIC-MODELS; DISPERSION MODEL; NITROGEN-DIOXIDE; Environmental Sciences & Ecology